Valorization of Underused Biomass of Acacia dealbata and Acacia melanoxylon Through Vermicomposting as an Alternative Substrate for Cucumber Production - Maria C. Morais; Elisabete Nascimento-Gonçalves; Tiago Azevedo; Henda Lopes; Helena Ferreira; Ana M. Coimbra; Berta Gonçalves; João R. Sousa; Marta Roboredo; Paula A. Oliveira (Recycling, 2025)
Invasive alien species are one of the main threats to global biodiversity, and pose significant management challenges in several areas outside their natural range. In southern Mediterranean Europe, the invasion of Acacia species is particularly severe and its control requires costly and often ineffective actions. The use of vermicompost derived from these species to replace peat-based substrates in horticulture offers a promising alternative to mitigate their economic and environmental impacts while enhancing the sustainability of their control. This study explored the potential of vermicompost produced from the fresh aboveground waste biomass (leaves + stems + flowers) of Acacia dealbata and Acacia melanoxylon (75:25 w/w), two of the most aggressive Acacia species in the Mediterranean, using Eisenia fetida over twelve weeks. In essence, this study aimed to evaluate the quality of the produced vermicompost and its suitability as a partial substitute for potting substrate in the production of cucumber (Cucumis sativus) seedlings for transplant. Four substrate mixtures containing 0%, 10%, 30%, and 50% of Acacia vermicompost (w/w), combined with commercial peat-based potting substrate and perlite (20%) were tested in polystyrene seedling trays. Seedling emergence, growth, and leaf biochemical parameters (photosynthetic pigments, phenolics, soluble sugars and starch, and total thiobarbituric acid-reactive substances—TBARSs) were evaluated. The results showed that the addition of Acacia vermicompost to the commercial substrate did not affect its germination but significantly enhanced seedling growth, particularly in mixtures containing 30% and 50% Acacia vermicompost. In addition, the absence of accumulation of TBARSs also reflected the superiority of these two treatments. These findings suggest that vermicompost derived from A. dealbata and A. melanoxylon biomass can be a viable peat-based substrate alternative for horticultural production, with the dual benefit of promoting sustainable agricultural practices and contributing to invasive species management.